World tables : 1989-90 edition - World Bank.; International Finance Corporation (Baltimore : Published for the World Bank by the Johns Hopkins University Press, 1976)
This edition of World Tables (WT) updates core socio-economic indicators given on country pages in 1988-89 edition, for the same set of countries -136 Bank members plus Switzerland.
"From the data files of the World Bank."
rpm 05/02/2019
Ref
Keywords: Economic history---Statistics; Economic indicators; Social indicators; Economic history; Economic conditions